The Supreme Court in the Early Republic : The Chief Justiceships of John Jay and Oliver Ellsworth - Casto, William R., 1946- (Book collections on Project MUSE., 2012)
An insightful look at the first Supreme Court and the controversies that surrounded the judicial body.